Anatomical and functional outcomes following switching from aflibercept to ranibizumab in neovascular age-related macular degeneration in Europe: SAFARI study. Issue 4 (5th August 2019) - Gale, Richard P; Pearce, Ian; Eter, Nicole; Ghanchi, Faruque; Holz, Frank G; Schmitz-Valckenberg, Steffen; Balaskas, Konstantinos; Burton, Ben J L; Downes, Susan M; Eleftheriadis, Haralabos; George, Sheena; Gilmour, David; et al.
Abstract : Background/Aims: Prospective data on switching anti-vascular endothelial growth factors in patients with neovascular age-related macular degeneration (nAMD) who have previously shown no/partial response are limited. This prospective study assessed the effect of switching from aflibercept to ranibizumab on anatomical and functional outcomes in patients with persistent/recurrent disease activity. Methods: SAFARI (NCT02161575 ) was a 6-month, prospective, single-arm study conducted in the UK and Germany. Patients, meeting strict eligibility criteria for one of two subgroups (primary treatment failure or suboptimal treatment response), received 3 monthly intravitreal ranibizumab injections (0.5 mg). Thereafter, ranibizumab was administered pro re nata at monthly visits. The primary endpoint was change from baseline (CfB) to day 90 in central subfield retinal thickness (CSRT). Best-corrected visual acuity (BCVA) and retinal morphology parameters were assessed. Results: One hundred patients were enrolled (primary treatment failure, 1; suboptimal treatment response, 99). In the overall population, there was a significant CfB in median CSRT of −30.75 µm (95% CI −59.50, –20.50; p<0.0001) to day 90. Improvements were also observed in other quantitative and qualitative optical coherence tomography parameters. In Early Treatment Diabetic Retinopathy Study letters assessed by category, 55% and 59% of patients gained 0–≥15 letters versus baseline at day 90 and day 180, respectively. However, mean improvements in BCVA (CfB) to each time point were small (≤2 letters). No new safety signals were identified. Conclusion: Switching from aflibercept to ranibizumab led to a significant improvement in CSRT, with 60% experiencing stabilised/improved BCVA. Therefore, patients with nAMD who have shown a suboptimal response to aflibercept may benefit from switching to ranibizumab.